An efficient visible-light photocatalyst prepared by modifying AgBr particles with a small amount of activated carbon. (April 2016) - Wang, Desong; Zhao, Mangmang; Luo, Qingzhi; Yin, Rong; An, Jing; Li, Xueyan
Graphical abstract: Highlights: An efficient visible-light photocatalyst was prepared by modifying AgBr particles. A small amount of activated carbon was used to modify AgBr particles. The modified AgBr exhibited improved visible-light photocatalytic performances. Abstract: An efficient visible-light photocatalyst was successfully prepared by modifying AgBr particles with a small amount of activated carbon (AC) via a simple chemical precipitation approach. The AC/AgBr composite was characterized by X-ray diffraction, X-ray photoelectron spectroscopy, scanning electron microscopy, UV–vis diffuse reflection spectroscopy, photoluminescence spectroscopy, electrochemical impedance spectroscopy. The photocatalytic performances of the AC/AgBr composite were investigated by evaluating photodegradation of methyl orange (MO) and phenol under visible light irradiation, and the effects of the AC content in the composite, concentrations of AC/AgBr composite and MO, carrier scavengers on MO photodegradation rate were systematically investigated. The results indicated that the modification of AC can hardly change the crystalline and crystal size of AgBr particles, while significantly improve their specific surface areas, visible-light absorption and separation efficiency of photogenerated electron–hole pairs. Compared with pure AgBr, the AC/AgBr composite exhibited drastically enhanced visible-light photocatalytic activity and stability. The photogenerated electrons and holes, hydroxyl radicals are responsible to the photodegradation of organic pollutants, and the photogenerated holes are the main active species. On the basis of the results and the properties of AC and AgBr, the visible-light photocatalytic mechanism of the AC/AgBr composite was discussed.